Radiance from Halcyon : a Utopian experiment in religion and science - Ivey, Paul Eli, 1959- (UPCC book collections on Project MUSE., 2013)
In May 1904, the residents of Halcyon-a small utopian community on California's central coast-invited their neighbors to attend the grand opening of the Halcyon Hotel and Sanatorium. As part of the entertainment, guests were encouraged to have their hands X-rayed. For the founders and members of Halcyon, the X-ray was a demonstration of mysterious spiritual forces made practical to human beings. Radiance from Halcyon is the story not only of the community but also of its uniquely inventive members' contributions to religion and science. The new synthesis of religi.